Notários e registradores na condição de intérpretes da Constituição: contribuições oferecidas para a promoção de direitos fundamentais - Negreiros, Danilo (2015)
Currently, Brazil is experiencing a maturing period of constitutional law. The promulgation of the 1988 Constitution brought also the need for a new theoretical structure able to better quench the need for execution of so many guarantees contained in the Constitution in contemporary society marked by increasing complexity. For that purpose, the constitutional science tends to overcome typical positivists precepts from the legislative State with rule of law of liberal nature. In this regard, constitutional scientists indicate that such post positivists advances are characteristic of the current constitutional State. Among those exceedances, this study highlights the constitutional interpretation performed by a variety of law applicators as a way to enhance the realization of the constitutional rights. Thus, under the force of a Constitution marked by high axiological load, inserted in a society without solid valorative consensus, this work points public registers and notaries as legal professionals who perform their duties under significant proximity of the fundamental rights of citizens and, therefore, can offer many contributions to the effectiveness of such rights if they exercise their functions based directly on the Constitution and the socio-cultural particularities of each case. However, the current tradition is a constitutionally timid performance of these professionals as a result of too detailed norms existing between the register or notary and the Constitution. This restriction to constitutional interpretation is retrograde and misplaced in the current Brazilian legal context. The phenomenon of this anachronism is studied from the perspective of the state of exception, according to which a normative order in may be suspended without having been formally revoked. The exception is an existing government technical applied in most contemporary democracies, according to scientists, and often aims at maintaining stability and order. Thus, the study argues that the current Brazilian legal context exceeded certain positivist thinking, which leads to the need for greater performance from several applicators of law, including notaries and registrers as a way to better enforcement of fundamental rights, however, this new constitutional post 9 positivist and pluralistic order is suspended informally, in order to allow the maintenance legal precepts of earlier times in the name of stability.